2020
DOI: 10.1186/s12870-020-02415-2
|View full text |Cite
|
Sign up to set email alerts
|

The loss of photosynthesis pathway and genomic locations of the lost plastid genes in a holoparasitic plant Aeginetia indica

Abstract: Background: With three origins of holoparasitism, Orobanchaceae provides an ideal system to study the evolution of holoparasitic lifestyle in plants. The evolution of holoparasitism can be revealed by plastid genome degradation and coordinated changes in the nuclear genome, since holoparasitic plants lost the capability of photosynthesis. Among the three clades with holoparasitic plants in Orobanchaceae, only Clade VI has no available plastid genome sequences for holoparasitic plants. In this study, we sequenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…A notable case is the plastome of Thismia thaithongiana , for which the equilibrium AT-content is approximately 92%. AT-content of plastid genes more than 90% is known for Balanophoraceae ( Schelkunov et al, 2019 ; Su et al, 2019 ; Chen et al, 2020 ), therefore it may be possible to actually achieve such a high AT-content. However, mutation spectra and selection in Thismia may change in the future thus making the current equilibrium AT-contents different from stable AT-contents that Thismia will finally reach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable case is the plastome of Thismia thaithongiana , for which the equilibrium AT-content is approximately 92%. AT-content of plastid genes more than 90% is known for Balanophoraceae ( Schelkunov et al, 2019 ; Su et al, 2019 ; Chen et al, 2020 ), therefore it may be possible to actually achieve such a high AT-content. However, mutation spectra and selection in Thismia may change in the future thus making the current equilibrium AT-contents different from stable AT-contents that Thismia will finally reach.…”
Section: Resultsmentioning
confidence: 99%
“…The variation of the overall plastome structure in heterotrophs of recent origin is typically minor. The middle stages of plastome reduction have been also extensively studied in both parasitic and mycoheterotrophic plants ( Wicke et al, 2016 ; Lallemand et al, 2019 ; Chen et al, 2020 ). These studies have shown that the patterns of gene loss in general follow the model of Barrett and Davis ( Barrett and Davis, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study was undertaken to determine the plastome and mitogenome of A. indica and to compare these with previously reported results [ 31 ], especially with respect to mitogenome size, gene, and intron contents and repeats, and to analyze the HGT, IGT, and CMS genes in the A. indica mitogenome.…”
Section: Introductionmentioning
confidence: 89%
“…Previous phylogenetic studies have shown that A. indica is united with Stiga , Buchera , Radmaea, and Harveya [ 29 , 30 ]. The plastome of A. indica has been reported to be 86,212 bp in size and to have lost almost all photosynthesis-related genes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesised that the chlorophyll may have some functions other than photosynthesis (Cummings & Welschmeyer, 1998). Analyses of transcriptomes and genomes showed that the pathways for synthesis and breakdown of the chlorophyll are indeed probably retained in some non-photosynthetic species (Wickett et al, 2011; Schelkunov, Penin & Logacheva, 2018; Marcin et al, 2020), though likely lost in some others (Ng et al, 2018; Schelkunov, Penin & Logacheva, 2018; Chen et al, 2020b). In Rhopalocnemis phalloides and Balanophora fungosa the RBH analysis indicates complete disappearance of chlorophyll synthesis and breakdown genes.…”
Section: Resultsmentioning
confidence: 99%